(3QSGdI aj GdaQb Hjf NWGH GdJcdja hNWGH GdhVYs - (3eMeO GdSYjO Hf eMjj GdOjf GdMSfj GdLRGFQj,J (B1278 (3g` s ((3YHO GdbGOQ Hf eMeO Hf jYbhH s)
(3ChdgG (B:s
(3GdMeO ddg Ydi LRjd fYeg hHYO aEfc EdJeSJ efi CjVkG GdaQb Hjf NWGH GdJcdja hNWGH GdhVY aGYde hdOi HGQc Gddg ajce hdc (B_ (3Cf GdMce ef MjK gh EKHGJ CeQ Ch fbjg Yfg s
(3BNQgG (B:s
(3bGd eDdag hcJH HChGNQ QeVGf ef YGe (B1276 (3g` QHfG dGJRZ bhdHfG HYO EP gOjJfG , hgH dfG ef dOfc QMeI Efc CfJ GdhgGH s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3CUhd Gdabgs